2016
DOI: 10.1002/esp.3882
|View full text |Cite
|
Sign up to set email alerts
|

Low impact surface hardness testing (Equotip) on porous surfaces – advances in methodology with implications for rock weathering and stone deterioration research

Abstract: The Equotip surface hardness tester is becoming a popular method for rock and stone weathering research. In order to improve the reliability of Equotip for on‐site application this study tested four porous limestones under laboratory conditions. The range of stone porosity was chosen to represent likely porosities found in weathered limestones in the field. We consider several key issues: (i) its suitability for soft and porous stones; (ii) the type of probe required for specific on‐site applications; (iii) ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 55 publications
0
38
0
Order By: Relevance
“…For example, Wilhelm et al (2016b) found much more variable data (and thus a need for much larger sample sizes) from four different British building limestones. For example, Wilhelm et al (2016b) found much more variable data (and thus a need for much larger sample sizes) from four different British building limestones.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, Wilhelm et al (2016b) found much more variable data (and thus a need for much larger sample sizes) from four different British building limestones. For example, Wilhelm et al (2016b) found much more variable data (and thus a need for much larger sample sizes) from four different British building limestones.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, values from probe D are expressed as HLD, and those from probe C as HLC (following the notation proposed by Wilhelm et al, 2016b). In this study, Probe D and Probe C have been used.…”
Section: Surface Hardness Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, an Equotip 3 with a D-type probe was used to map variations in weakening of the stone surface. This equipment was originally developed for the testing of metals [22], but is now used in both natural settings [23,24] and the built environment [25]. The surface hardness is measured through rebound of a 3 mm diameter spherical tungsten carbide test tip against the rock surface.…”
Section: Methodsmentioning
confidence: 99%